Gambaran Status Gizi pada Balita di Puskesmas Karang Harja Bekasi Tahun 2019 - Nurshifa Eka Putri; Mia Yasmina Andarini (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. Humans, especially toddlers, need good nutritional status. Nutritional status is the state of the body due to food consumption and use of nutrients, which is defined as the balance of energy that is entered and released by the body. The health profile of Bekasi Regency in 2017 shows that there are 3.88% of children under five with malnutrition status and 0.04% with malnutrition status. And 2.91% of children under five with more nutrition. This study aims to determine the nutritional status of children under five at Puskesmas Karang Harja Bekasi in 2019. This study uses a descriptive research method with a cross sectional design that measures variables as well as to determine the nutritional status of children. Sampling of this research is a total sampling technique from recording data reporting months of weighing toddlers aged 12-60 months at Puskesmas Karang Harja Bekasi in 2019. This research was conducted from September to December 2020. The results of this study indicate that children under five at Puskesmas Karang Harja Bekasi in 2019 as many as 902 people, 771 people with good nutrition (85.5.3%), 62 people (7.9%) with good nutrition, 59 people (6.5%)% malnutrition and ten people (1.1%) ) malnutrition. This study concluded that the nutritional status of children under five was mostly good. However, there are still children with low nutritional status, so it should be noted that there are still many malnourished children under five in Indonesia. Abstrak. Manusia khususnya balita membutuhkan status gizi yang baik. Status gizi adalah keadaan tubuh sebagai akibat dari konsumsi makanan dan penggunaan gizi, yang didefinisikan sebagai keseimbangan energi yang masuk dan dilepaskan oleh tubuh. Profil kesehatan Kabupaten Bekasi tahun 2017 menunjukkan terdapat 3,88% balita dengan status gizi buruk dan 0,04% dengan status gizi buruk. Dan 2,91% balita dengan gizi lebih. Penelitian ini bertujuan untuk mengetahui status gizi balita di Puskesmas Karang Harja Bekasi tahun 2019. Penelitian ini menggunakan metode penelitian deskriptif dengan desain cross sectional yang mengukur variabel dan untuk mengetahui status gizi balita. Pengambilan sampel dalam penelitian ini adalah teknik total sampling dari pencatatan data pelaporan bulan penimbangan balita usia 12-60 bulan di Puskesmas Karang Harja Bekasi tahun 2019. Penelitian ini dilakukan pada bulan September hingga Desember 2020. Hasil penelitian ini menunjukkan bahwa balita di Puskesmas Karang Harja Bekasi tahun 2019 sebanyak 902 orang, gizi baik 771 orang (85.5,3%), gizi baik 62 orang (7,9%), gizi baik 59 orang (6,5%)% dan gizi buruk sepuluh orang ( 1,1%)) malnutrisi. Studi ini menyimpulkan bahwa status gizi balita sebagian besar baik. Namun demikian, masih terdapat balita dengan status gizi rendah, sehingga perlu diperhatikan bahwa masih banyak balita gizi buruk di Indonesia.